PREDICTION OF PH IN NATURAL HYDROTHERMAL FLUIDS AT ELEVATED P-T CONDITIONS - Roberts S.J. (My University, 1998)
The pH of fluids at elevated temperature-pressure conditions are routinely calculated from fluid compositions measured in the laboratory. Numerical errors, uncertainties in thermodynamic data, and analytical errors can affect these computed values. An analysis of pH values computed at elevated temperature and pressure conditions for natural fluids reveals that the amount of error in computed pH values can be, but is not always, dependent on fluid composition. Not all reactions occurring in a fluid affect computed pH values. Therefore, inadequacies in the thermodynamic properties of a species may affect computed pH values in some fluid compositions but not others. When a single reaction controls the production/consumption of H+, the amount by which the pH changes as a function of temperature and pressure is independent of the measured pH. However, when two or more reactions produce/consume sufficient H+ to change the pH, the amount by which the pH changes as a function of temperature and pressure is dependent on the measured pH. Uncertainties in the measured pH are magnified as temperature and pressure increase for some fluid compositions, while the uncertainty decreases in others. When small uncertainties in the measured pH are magnified, the activities of aqueous species calculated at elevated temperature and pressure conditions cannot be used to predict fluid-mineral equilibria.
Keywords: PH VALUES; ELEVATED TEMPERATURE-PRESSURE CONDITIONS; FLUID-MINERAL EQUILIBRIA